The biased adenosine-rich content of the HIV-1 genome serves as a molecular signature that facilitates efficient packaging - Hung R. Vuong; Qianzi Zhou; Sydney L. Lesko; Kasyap Tenneti; Keanu Davis; Shanyqua Scott; Moming Guo; Daphne Boodwa-Ko; Jenna E. Eschbach; Kamya Gopal; Jessica M. Porter; Qibo Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
The HIV-1 genome [genomic RNA (gRNA)] has an unusually biased nucleotide content and is rich in adenosines. Selective packaging of the gRNA is thought to be driven by specific binding of the nucleocapsid (NC) domain of the viral Gag protein to the packaging signal (Ψ) in the host cell cytosol. However, deletion of regions within Ψ reduces—but does not completely abolish—genome packaging. To probe whether another feature of the gRNA may contribute to the selective gRNA packaging process, we replaced NC with heterologous RNA-binding domains (RBDs) with distinct RNA-binding properties. Surprisingly, despite disparate RNA binding specificities, all Gag-RBD chimeras successfully recruited the gRNA to the plasma membrane, suggesting that the initial gRNA recognition in the cytosol is not rate limiting. Notwithstanding, many chimeras exhibiting G/C binding specificity were arrested at the assembly stage. Only the Gag-SRSF5 chimera, which multimerized efficiently on adenosine-rich sequences on the gRNA, assembled efficiently and packaged gRNA at near wild-type levels. Importantly, rationally designed mutations that altered the A/G-rich binding specificity of Gag-SRSF5 decreased genome encapsidation efficiency. Furthermore, many Gag chimeras displayed potent dominant negative activities, highlighting NC functions as a targetable step in virus replication. Together, our findings reveal an unexpected aspect of the HIV-1 gRNA, its biased nucleotide content, as a key driver of selective genome packaging.